The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/sym12050837
|View full text |Cite
|
Sign up to set email alerts
|

A New Energy Efficient Multitier Deterministic Energy-Efficient Clustering Routing Protocol for Wireless Sensor Networks

Abstract: Wireless Sensor Networks (WSNs) may be incorporated with thousands of small nodes. This gives them the capability to effectively sense, communicate, and compute parameters. However, the security and life span of a WSN node is a primary concern. This paper is focused on introducing a mathematical model of a modified Multitier Deterministic Energy-Efficient Clustering (DEC) based on novel election multi-tier random probability protocol for agricultural WSNs to enhance the life span of a WSN node along with a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A birthday assault is a type of attack using the mathematics behind the birthday problem [20]. The birthday paradox principle considered that specific pairs in a randomly selected group of people are likely birthday-friendly [21]. Rainbow tables are extensive data collections that store various common and weak passwords and hashes generated using those passwords.…”
Section: Overview Of Managing Data Security Using Keyed-hash Message Authentication Code-based Encryption Algorithmmentioning
confidence: 99%
“…A birthday assault is a type of attack using the mathematics behind the birthday problem [20]. The birthday paradox principle considered that specific pairs in a randomly selected group of people are likely birthday-friendly [21]. Rainbow tables are extensive data collections that store various common and weak passwords and hashes generated using those passwords.…”
Section: Overview Of Managing Data Security Using Keyed-hash Message Authentication Code-based Encryption Algorithmmentioning
confidence: 99%
“…Simulation results showed that their models increase the energy efficiency and extend the network lifespan. Koyuncu et al [72] explained several WSN probabilistic routing protocols including LEACH. They selected CHs based on the energy drain pattern and location of the sensor nodes, which increased the lifespan of sensor nodes.…”
Section: Lifespan Related Algorithmsmentioning
confidence: 99%
“…The sensor nodes based on activity are energy-dependent, therefore coverage and energy consumption of the entire network are considered as the two significant parameters in WSN. 16 The significant intention of designing a WSN involves transferring the data among the sink node thereby maintaining stable communication among the sensors and enhancing the network lifetime. 17 This article aims in proposing a novel protocol for enhancing the energy efficiency of the network thereby providing an optimal routing path by selecting the optimal cluster head which maintains communication among the base station and the sensor node to enhance the network lifetime.…”
Section: Introductionmentioning
confidence: 99%